Funciones distance decay y Sistemas de Información Geográfica (SIG) para la estimación de demanda potencial en el Transporte Público de Resistencia (Chaco, Argentina) - Cardozo, Osvaldo Daniel (2015)
The levels of accessibility in public transportation are a critical element to evaluate and planning the service. Increase awareness of this situation can lead to substantial improvements in access opportunities by users, especially at local level, what is very difficult in the classical aggregate transport models. In this way, our model proposes to focus the analysis of the travel demand to transportation at the bus stop level, combining an intensive fieldwork to collect date and the use of GIS tools to calculate variables, such as reached distance for obtain a model demand. The aim of the paper is to analyse the volume of passengers that access to public transportation at each bus stop in Resistencia and the distances walked to them. This seeks to reconstruct the spatial behaviour of passengers at the local level through an empirical function, known as distance decay curve.